A thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel and a method for manufacturing the steel with reduced edge pitting
By optimizing the composition and process flow of hot-dip galvanized phosphated steel, the problem of pitting defects on the edges of thin-spec steel plates is solved, and the product surface quality and production efficiency are improved.
Patent Information
- Application Number
- CN202310048303.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-01-31
AI Technical Summary
When producing hot-dip galvanized phosphated steel, pitting defects are prone to the edges of thin-spec steel plates, which affects the coating performance and quality of the product.
By optimizing the steel composition and process flow, including iron pretreatment, converter smelting, hot rolling, pickling and cold continuous rolling and continuous annealing, the composition and temperature of the steel plate are controlled, the formation of iron oxide sheet and the precipitation of oxides are reduced, and zinc is ensured. Good wetting of liquid and steel matrix.
It effectively reduces the generation of pockmarks on the edges of the steel plate, improves the surface quality of the product, meets the strict requirements of automobile parts, simplifies the production process, and improves production efficiency.
Smart Images

Figure CN116287976B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of steel rolling, and particularly relates to a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel and a manufacturing method for reducing pitting on its edges, which is a full-process manufacturing method for reducing pitting on the edges of thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with a yield strength of 190 MPa. Background Art
[0002] Hot-dip galvanized phosphating steel is an economical high-strength steel plate, which is widely used in the production of automobile door panels, hoods and other parts. Since strengthening elements such as P, Mn, and Si must be added to the steel to ensure that the basic strength meets the requirements. However, these elements will show different degrees of precipitation behavior during the continuous annealing process as the atmosphere in the furnace changes, thereby affecting the hot-dip galvanizing reaction. This has been fully studied at home and abroad.
[0003] In the actual production process, it is found that this type of steel is prone to pitting defects on the edge of the steel strip. This defect is not accepted by customers as an appearance part, which mainly affects the coating performance of the product. Conventional phosphating film cannot fully cover it. Large-scale industrial production often causes excessive quality losses due to pitting problems during the mass production of this type of galvanized sheet products.
[0004] Therefore, how to reduce the occurrence of such defects becomes an important issue to further improve the surface quality of this type of galvanized sheet. Summary of the invention
[0005] The purpose of the present invention is to provide a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel and a method for manufacturing the steel with reduced edge pitting. By designing the composition and process, the idea of linking the key manufacturing process nodes of the whole process is adopted to ensure that the probability of pitting on the surface of the final product is minimized. The product is suitable as an automotive component with extremely stringent requirements on surface quality.
[0006] The specific technical solutions of the present invention are as follows:
[0007] A thin gauge hot-dip pure zinc coated phosphorus-containing high-strength IF steel comprising the following components in mass percentage:
[0008] C 0.001~0.003wt%, Si 0.03~0.07wt%, Mn 0.3~0.4wt%, Al 0.03~0.06wt%, P 0.032~0.055wt%, B 0.0002~0.0006wt%, Nb 0.01-0.02wt%, Ti0.02-0.03wt%, S≤0.006wt%, N≤0.003wt%, and the balance is Fe and unavoidable impurities.
[0009] The thickness of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel is in the range of 0.6 mm to 0.8 mm;
[0010] The composition of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel satisfies: mass ratio P / B=53-275;
[0011] The present invention provides a method for manufacturing a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with reduced edge pitting, comprising the following process flow: molten iron pretreatment → converter smelting → alloy fine-tuning station → RH → continuous casting → hot rolling → pickling and cold rolling → continuous annealing → hot-dip galvanizing.
[0012] The continuous casting produces a rectangular ingot with a thickness of 230 mm ± 5 mm, a length of 20 ± 2 m, and a width of 1500-1900 mm, and uses an oxygen-acetylene flame to clean the surface iron oxide scale of the six faces of the rectangular ingot, with a cleaning thickness of 2-3 mm, so as to prevent the surface iron oxide scale and inclusions from being pressed into the steel matrix during the subsequent rolling process;
[0013] The hot rolling, slab heating is the first process of hot rolling, in order to eliminate the defects of the cast billet and reduce the deformation resistance of the steel. The rolling system of 6 rough rolling passes + 7 finishing rolling passes is adopted to reasonably distribute the rolling load and realize controlled rolling. The hot rolling furnace temperature is 1180-1210℃, the finishing rolling temperature is controlled at 1050-1080℃, the finishing rolling temperature is controlled at 1070-1100℃ within the range of 0-15cm of the edge, the temperature within the range of 0-15cm of the edge after finishing rolling is controlled at 920-935℃, and the temperature of the remaining parts is controlled at 910-925℃. Too low furnace temperature will lead to more heat loss at the last pass of finishing rolling. The temperature of the plate is too low, and a mixture of ferrite grains and austenite grains appears in the two-phase region of ferrite and austenite, resulting in poor uniformity of grain size. Since the heat exchange rate with the cold air in the surrounding environment within the range of 15cm of the edge is large, the temperature reduction rate is faster than that in the middle. The edge 0-15cm range refers to the range of 0-15cm from the edge. The edge directly exchanges heat with the cold air, and the cooling rate is greater than that of the middle. It is necessary to increase the edge temperature in advance to reduce heat loss. The coiling temperature is 620-650℃, and the Fe 2 O 3 Thickness ≤ 5μm, the entire iron oxide scale, including FeO+Fe 3 O 4 +Fe 2 O 3The total thickness is ≤10μm, which is convenient for controlling the elongation of the straightening process in the subsequent pickling and straightening process to ensure that the crack depth is ≤10μm, so that the acid can completely penetrate the entire oxide scale and remove it from its root. On the other hand, it can also ensure that a sufficient amount of smaller-sized NbC and TiN second phase particles are precipitated to hinder the migration and growth of grain boundaries, forming fine and uniform ferrite grains. The advantage of this is that the grain size can be increased by more than 0.5 levels. Under the premise of ensuring that the product performance meets the requirements, the addition of corresponding P, Si, and Mn strengthening elements can be reduced, further reducing the amount of oxide precipitation in the continuous annealing process.
[0014] During the pickling and cold rolling, in order to fully ensure that there is enough deformation energy storage during the annealing process and allow the favorable texture to fully develop, for the typical thickness of 0.6-0.8mm of the deep-stamping steel for the outer cover, the cold rolling reduction rate is not less than 75%, and the cold rolling reduction rate does not exceed 82% considering the rolling mill capacity. Therefore, the total reduction rate of the five stands used in the present invention is not less than 75% but not more than 82%. The straightening elongation of the pickling and cold rolling process is controlled at 1.5-2.5%. After straightening, the maximum depth of the iron oxide scale on the surface of the plate can reach 10μm. The roughness Ra of the steel plate after pickling is 0.4-0.8μm, the residual oil content at any position on the upper and lower surfaces is less than 100mg / L, the residual iron content is less than 50mg / L, and the pickling reflectivity at any position meets ≥75%.
[0015] The continuous annealing adopts short-time heating + low-temperature heat preservation + rapid cooling technology, specifically: uniform heating temperature is controlled at 780-800°C, uniform heating time is 55-60s, firstly slowly cools to 600-660°C at a slow cooling rate of 5.95°C / s-6.7°C / s; then rapidly cools to 11.9°C / s
[0016] ~14.6℃ / s cooling to 470~490℃; the dew point of the uniform heating section is -30~-20℃, which inhibits the formation of complex oxide films of Mn, B, and Si on the surface of the steel matrix in contact with the protective gas and cannot be reduced by the protective atmosphere in the furnace. The composition of the protective atmosphere in the heating furnace is H 2 Volume content 3%~7%, N 2 The volume content is 93% to 97%, O 2Volume content <0.001%. Isolating the zinc liquid from causing local leakage plating, the oxygen content in the furnace is guaranteed to be ≤10ppm during the entire annealing process, reducing the probability of oxygen atoms reacting with alloy elements in the steel, and preventing the formation of a network-like Mn, B, and Si oxide film connected together. Instead, a small "oxide film island" is formed near the grain boundary with a diameter of ≤10μm, which is slightly smaller than the grain size of 15-25μm, so that it cannot completely cover the entire grain, thereby avoiding the formation of a continuous network, and achieving the effect of enhancing the good wetting of the steel matrix and the zinc liquid. The method of low-temperature rapid cooling can also refine the ferrite grains, improve the strength of the steel matrix, and further reduce the amount of alloy elements added. Since the flow rate of gas will be greatly reduced when encountering a rough gas-solid interface, especially when the bearing seal is poor, even if the furnace is under positive pressure, outside air will enter the furnace through the leakage point and come into contact with the edge steel strip surface to cause alloy element oxidation. Therefore, the roughness Ra of the refractory brick surface of the annealing furnace wall needs to be controlled below ≤0.3μm, so as to ensure a large gas flow rate near the furnace wall and prevent outside air from entering the furnace.
[0017] For the hot-dip galvanizing, the temperature of the zinc pot is between 465 and 475°C, the dew point of the furnace nose is -6 to -3°C, and the temperature of the zinc pot is 453±2°C.
[0018] The production method of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel is 4 target rolls + 1 IF steel transition roll; the IF steel transition roll is an IF steel without alloy addition, which can be DC53D+Z, DC54D+Z, DC56D+Z or DC57D+Z steel;
[0019] The thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel produced by the present invention has a metallographic structure of ferrite, an average grain size of 8.5-9.5, a grain size of 15-25 μm, and an "oxide film island" formed near the ferrite grain boundary with a diameter of ≤10 μm; a yield strength of ≥190 MPa, a tensile strength of ≥350 MPa, an elongation after fracture of 38-45%, a work hardening rate n value of not less than 0.21, and a strain hardening index r 90 Not less than 2.0; within the 15cm width range on both sides of the steel plate, there are no more than 2 pits with a diameter of ≤0.4mm in every 3 meters of strip steel.
[0020] The design ideas of the present invention are as follows:
[0021] C: For ultra-low carbon IF steel, it should be as low as possible. However, when the C content is lower than 0.001wt%, the product has too few interstitial C atoms, which will lead to a sharp decrease in the amount of C compounds such as Nb and Ti. In the hot rolling coiling process, the grain boundary is clean, and there are not enough second-phase particles to prevent the rapid growth of grains. It is easy to have excessively coarse grains and inherit them to the continuous annealing process. The product strength will drop significantly. At this time, more alloying elements need to be added to ensure the strength, which is not economical for large-scale production. In addition, such a low C content also puts forward strict requirements on the refining process of molten steel, requiring a longer deep decarburization process, which is not an economical approach. Therefore, the appropriate C content range is 0.001-0.0030wt%. If it exceeds 0.0030wt%, the r value will drop sharply. At the same time, more microalloying Ti and Nb elements need to be added to increase the cost, which is not conducive to obtaining good deep drawing performance.
[0022] Si: An economical and effective solid solution strengthening element. For high-strength IF steel, adding a certain amount of Si can reduce the yield strength ratio and increase the uniform elongation. However, as the Si content increases, it is easy to enrich and generate SiO on the surface. 2 This oxide cannot be reduced by Al in the continuous annealing atmosphere and zinc solution, which is particularly detrimental to the wettability of the steel strip and the zinc solution. Improper process control will also cause surface defects such as plating leakage, so it needs to be controlled at a low level. Considering the difficulty of controlling performance and surface quality, the Si content in the present invention is 0.03-0.07wt%.
[0023] Mn: A beneficial and economical solid solution strengthening element in steel. The diameter of Mn atoms is equivalent to that of Fe atoms. All of them improve strength by solid solution strengthening. Although the strengthening effect of Mn is slightly weaker than that of P, it does not affect secondary brittleness. The presence of Mn atoms will reduce the activity of P atoms, avoid excessive grain boundary segregation, and reduce the recrystallization temperature, so the annealing temperature can be set at a lower level. Therefore, considering the performance and cost, the Mn content in the present invention is 0.3-0.4wt%.
[0024] P: The most economical and effective alloy element to improve product strength. On the one hand, it can improve strength by replacing Fe atoms to produce a large amount of distortion near the normal lattice. On the other hand, it can produce solid solution strengthening in the form of interstitial atoms. This strengthening effect is much higher than the solid solution strengthening of substitution type. Excessive addition of P will cause the yield increase rate to be higher than the tensile increase rate, which is not conducive to reducing the yield strength ratio and improving uniform elongation. Excessive P content will also greatly increase the risk of hot rolling and cause steel piling, especially for hot coils with a production width of more than 1800mm. P atoms have a small diameter and are prone to segregation to the grain boundary, increasing the risk of brittleness in secondary processing. Brittle fracture in severe cold environments increases safety hazards. Excessive P content will also make the degreasing process before the strip enters the annealing furnace difficult to clean. The surface reflectivity is more than 5% lower than that of ordinary IF steel. Surface dirt is brought into the annealing furnace to pollute the furnace rollers. In the continuous galvanizing annealing process, P will precipitate to varying degrees, especially in a fairly wide temperature range of 400-800℃, and will also precipitate Mn together with Mn. 3 (PO 4 ) 2 This characteristic will not only consume Mn atoms and reduce the strengthening effect of Mn, but also cause the oxide and Si and B oxides to continuously adhere to the surface of the furnace roller during the relative friction between the strip and the furnace roller. Long-term production will cause scarring on the surface of the furnace roller, thereby producing pressure pits on the surface of the strip. During the galvanizing process, the zinc liquid in the pressure pits is easily blown out by the air knife, resulting in small leakage points, which seriously affects the surface quality. Therefore, the P content must be strictly controlled. In order to take into account both mechanical properties and surface quality, the most suitable range of P content is 0.032-0.055wt%.
[0025] Al: Al is a common deoxidizer in steel. If the Al content is too low, coarse Mn and Si oxides will increase, reducing the purity of the steel; if the Al content is too high, aluminum oxide inclusions will increase, damaging the plasticity of the steel and increasing the difficulty of smelting and casting. At the same time, AlN particles formed by combining with N can pin the grain boundary and play a certain role in refining the grains. The Al content in the present invention is 0.03-0.06wt%.
[0026] Ti: In the steel of the present invention, it is mainly used to fix free N atoms in the smelting process. Since Ti preferentially combines with N to form TiN, which is a high-temperature precipitation type oxide, it can be completely precipitated in the finishing stage. Too little Ti cannot completely fix N atoms, which is not conducive to improving aging properties. Too much Ti will increase manufacturing costs and will oxidize during the annealing process to affect wettability with zinc liquid. The Ti content in the present invention is 0.02-0.03wt%.
[0027] Nb: The reason for choosing Ti+Nb composite component design is mainly to utilize Nb to combine with C atoms to generate NbC, which is dispersed and precipitated in the hot rolling coiling stage, and can be precipitated in large quantities with TiN precipitated in the finishing rolling stage as nucleation particles, preventing the rapid growth of grains, achieving the purpose of grain refinement, improving strength without losing too much ductility, and appropriately reducing the addition of other alloying elements to reduce the selective oxidation precipitation in the annealing process that affects wettability. In addition to having small planar anisotropy and stable mechanical properties, this component also has good resistance to coating powdering. The solid solution Nb is concentrated on the steel grain boundary and surface, which can reduce the grain boundary concentration of P and the surface enrichment of Mn. Therefore, it is very suitable for hot-dip galvanized sheets, but excessive addition of Nb will increase costs. The Nb content designed in the present invention is 0.01-0.02wt%.
[0028] B: It preferentially segregates to the grain boundary to reduce the grain boundary energy, avoiding excessive P segregation affecting the secondary cold working brittleness. However, if too much B is added, it will be oxidized to form MnB in the annealing furnace. 2 O 4 The oxide is difficult to be reduced and precipitates on the surface like P, which deteriorates the wettability of the strip steel and the zinc liquid. In severe cases, it will cause leakage plating and prevent recovery and recrystallization, reducing deep drawing performance. Therefore, the addition amount must be controlled at an extremely low level. The B content of the patent of this invention is controlled at 0.0002-0.0006wt%.
[0029] S, N: S can cause hot brittleness. Although it will combine with Mn to form MnS to reduce hot brittleness, it will consume Mn and reduce the strengthening effect of Mn. Therefore, it must be strictly controlled to the lowest level. N exists in the form of interstitial atoms similar to C. Ti or Nb must be added to fix and remove to avoid aging. The S content in the present invention is ≤0.006% and the N content is ≤0.003%.
[0030] The inventors found that the occurrence of pitting defects on the edge is closely related to the composition design of the steel grade, hot rolling, acid rolling and the whole process of galvanizing. The main reason is that the edge of the strip has poor wettability, resulting in poor adhesion between the zinc liquid and the substrate in the micro-area where the inhibition layer is locally lacking. Under the action of gravity, it flows and gathers in the opposite direction of the strip. After cooling, it cannot be leveled, resulting in a thin zinc layer near it and leaking spots, which show the shape of pitting on a macro scale. At present, there are few patents and papers on the overall design and optimization of the whole process manufacturing process for the pitting of the edge of 190MPa grade phosphated steel galvanized steel sheets at home and abroad. The core goal of the patent of this invention is to start from the top-level design of the product, propose an innovative manufacturing method from the perspective of the whole process, and optimize the design of key manufacturing process points, so as to ensure that there are no or very few pitting on the edge of the final galvanized sheet product, meet the needs of large-scale industrial production and car factories, reduce losses, improve production efficiency and reduce costs.
[0031] The present invention ensures that the C content in the steel is between 0.001 and 0.003 wt%. Too low a C content is not conducive to the formation of a sufficient number of NbC and TiN particles, and too high a C content will cause the plasticity of the steel plate to deteriorate. Therefore, the design idea is to have a sufficient amount of C and N atoms while having ultra-low carbon. The Nb+Ti composite component design is used to fix the residual C and N atoms in the steel to form a large number of fine NbC and TiN grain boundary precipitates to refine the ferrite grains and ensure the strength of the steel plate. The total addition amount is ≤0.05 wt% to avoid excessive cost increase. The addition amount of B is strictly controlled at 2 to 6 ppm to minimize the addition of MnB in the continuous annealing process. 2 O 4 The formation of oxides, on the one hand, reduces the additional consumption of Mn and weakens the solid solution strengthening effect, on the other hand, B is easily oxidized in an oxygen-rich environment and the generated compounds cannot be oxidized by 3% to 7% H 2 +93%~97%N 2 The protective gas reduction of the composition, these compounds float on the surface of the annealed plate to hinder the normal diffusion reaction of Fe-Zn, making the wetting angle between the annealed steel plate and the zinc liquid larger and difficult to wet. The weight wt% ratio of P / B is controlled between 53 and 275. If it is too small, it will cause a large number of B to preferentially concentrate at the grain boundary, making it more easily oxidized.
[0032] The present invention adopts a lower furnace discharge temperature to reduce the amount of iron oxide scale generated in the slab. Since the hot-rolled plate of the thin-gauge galvanized sheet product is also thin, usually below 4.0 mm, a too low furnace discharge temperature will result in a large amount of heat loss at the last pass of finishing rolling. The temperature is too low and a mixture of ferrite grains and austenite grains appears in the two-phase region, resulting in poor uniformity of grain size. The temperature within the 15 cm range of the edge drops rapidly, and it is necessary to control the temperature of the remaining parts in a zone. Therefore, the furnace discharge temperature needs to be controlled at 1180-1210°C and the finishing rolling temperature needs to be controlled at 1050-1080°C. The finishing rolling temperature within the range of 0-15 cm of the edge is controlled at 1070-1100°C, ensuring that the temperature of the steel plate is always maintained within the full austenitization temperature range during the entire finishing rolling process. The temperature within the range of 0-15 cm of the edge at the end of finishing rolling is controlled at 920-935°C, and the temperature of the remaining parts is controlled at 910-925°C.
[0033] The present invention adopts a lower coiling temperature to ensure that the thickness of the iron oxide scale at any position on the surface of the hot-rolled plate is ≤10μm, which is convenient for controlling the elongation of the straightening process in the subsequent pickling and straightening process to ensure that the crack depth reaches 10μm, so that the acid can completely penetrate the entire iron oxide scale and remove it from its root. Therefore, the coiling temperature is preferably controlled at 620-650℃ to reduce the Fe oxide scale on the surface of the hot-rolled plate. 2 O 3 The thickness is controlled at ≤5μm, and the entire iron oxide scale, including FeO+Fe 3O 4 +Fe 2 O 3 The total thickness is controlled at ≤10μm. In addition, sufficient NbC and TiN second-phase particles of smaller size can be precipitated to hinder grain boundary migration and growth, forming fine and uniform ferrite grains. The advantage of this is that the grain size can be increased by more than 0.5 levels. Under the premise of ensuring that the product performance meets the requirements, the addition of corresponding P, Si, and Mn strengthening elements can be reduced, further reducing the amount of oxide precipitation during the continuous annealing process;
[0034] The present invention has a pickling and cold rolling process with a straightening elongation of 1.5-2.5%, which ensures that the depth of the iron oxide scale reaches 10 μm, and the roughness Ra of the steel plate after pickling is 0.4-0.8 μm, which reduces the maximum depth of the tiny peaks and valleys on the surface of the steel plate, prevents the rolling oil from remaining in the deeper peaks and valleys and being difficult to be removed by subsequent alkali washing and electrolytic cleaning, and the residual oil amount at any position on the upper and lower surfaces is less than 100 mg / L, the residual iron amount is less than 50 mg / L, and the pickling reflectivity at any position satisfies ≥75%, thereby achieving the purpose of reducing surface oil pollution to the greatest extent;
[0035] The annealing of the present invention adopts short-time heating + low-temperature heat preservation + rapid cooling technology, the uniform heating time is controlled at 55-60s, the heat preservation temperature is controlled at 780-800°C, the slow cooling rate is controlled at 5.95°C / s-6.7°C / s, and the temperature is slowly cooled to 600-660°C; then the temperature is cooled to 470-490°C at a rapid cooling rate of 11.9°C / s-14.6°C / s, and the dew point of the uniform heating section is controlled within the range of -30--20°C to inhibit P, Mn, B, and Si from forming a complex oxide film on the outermost surface of the steel substrate in contact with the protective gas, which cannot be reduced by the protective atmosphere in the furnace, isolates the zinc liquid and causes local leakage plating, and under the process conditions, 80% of the oxides of the above elements are transferred from the outermost surface to the subsurface within 100nm below the steel strip. The oxygen content in the furnace of the uniform heating and cooling section is guaranteed to be ≤10ppm, which reduces the probability of oxygen atoms reacting with alloy elements in steel and prevents the formation of a network-like Mn, B, and Si oxide film. Instead, a small "oxide film island" is formed near the grain boundary with a diameter of ≤10μm, which is slightly smaller than the grain size of 15-25μm, so that it cannot completely cover the entire grain, thereby avoiding the formation of a continuous network and achieving the effect of enhancing the good infiltration of the steel matrix and the zinc liquid. The method of low-temperature rapid cooling can also refine the ferrite grains, improve the strength of the steel matrix, and further reduce the amount of alloy elements added;
[0036] At present, the furnace walls of vertical annealing furnaces are mostly made of refractory bricks with relatively rough surfaces. The uniform heating process of the steel strip is the core stage of grain growth and annealing and diffusion of alloy elements. Gas convection is inevitable between the furnace roller bearings and the furnace atmosphere. Therefore, in most cases, the annealing furnace maintains a slightly positive pressure state to prevent the backflow of external air. However, it cannot be ignored that the roughness of the furnace wall must be controlled. This is mainly because the gas flow rate will be greatly reduced when encountering a rough gas-solid interface. Especially in the case of poor bearing sealing, even if the furnace is positively pressurized, external air will enter the furnace along the leakage point and contact the edge steel strip surface to cause oxidation of alloy elements. Therefore, the roughness Ra of the refractory brick surface of the furnace wall needs to be controlled below ≤0.3μm, so as to ensure that the gas flow rate near the furnace wall is large and prevent external air from entering the furnace by convection.
[0037] Even if the above process control is met, a certain amount of oxide will still precipitate from the strip during the continuous annealing process and adhere to the surface of the furnace roller. Some of it can be taken away with the movement of the strip, but the oxide adhesion to the furnace roller is a dynamic balance process. As the production time increases, the amount of oxide adhering to the surface of the furnace roller will inevitably exceed the part taken away by the strip, thus breaking this balance and causing excessive and hard Mn to adhere to the surface of the furnace roller. 3 (PO 4 ) 2、 MnB 2 O 4 Oxides such as rust and dents appear on the surface of the furnace roller, and pits appear on the surface of the strip. When passing through the air knife, local gas turbulence near the pits will also cause pitting. Therefore, in order to ensure sustainable production when producing phosphating steel, it is necessary to add IF steel without alloy addition as a transition roll in the continuous production process to take away excess oxides on the surface of the furnace roller. This can avoid excessive continuous production to break the balance between the amount of oxide adhesion and the amount of steel strip taken away. The most economical and suitable production method is 4 target rolls + 1 transition roll.
[0038] Compared with the prior art, the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with a yield strength of 190 MPa produced by the present invention can meet the metallographic structure of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with a yield strength of 190 MPa for a thickness of 0.6 to 0.8 mm, which is ferrite with an average grain size of 8.5 to 9.5 and a grain size of 15 to 25 μm. The diameter of the "oxide film island" formed near the ferrite grain boundary is ≤10 μm; the elongation after fracture is 38 to 45%, the work hardening rate n value is not less than 0.21, and the strain hardening index r 90Not less than 2.0. There are no more than 2 pits with a diameter of ≤0.4cm in every 3-meter strip within the 15cm width of both sides of the steel plate. The surface quality meets the extremely stringent requirements of automotive panels, and has the advantages of simple production process operation, stable and reliable product quality, and energy saving and emission reduction. It can be widely promoted and applied in galvanizing production lines. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The hot rolled coil oxide scale of Example 1, the average value of any three points is 9.37 μm, and the surface layer (white) Fe 2 O 3 Thickness: 2 μm;
[0040] Figure 2 This is a schematic diagram of the acid-rolling and straightening of the oxide scale cracks reaching 10μm and the acid flowing into the root to remove them;
[0041] Figure 3 The annealing production process of Example 1; wherein the RTF section and the cooling section (SCS, RCS) are 2 Content <10ppm, uniform heating temperature 795℃, uniform heating section dew point -27.8℃;
[0042] Figure 4 The oxide film of Example 1; the oxide film diameter is less than the grain, and does not completely cover the grain;
[0043] Figure 5 This is the macroscopic morphology of the pits in Example 1, with a diameter of 0.4 mm (compared with the standard pit gauge);
[0044] Figure 6 The chemical composition analysis of the pits in Example 1 shows that the content of Mn and Si is greater than that of the matrix, and there is precipitation;
[0045] Figure 7 The annealing process of the pit severity comparison example 1 is shown in FIG. 2 Content>10ppm, RTF>-20℃, different atmosphere and dew point from the requirements of the invention, resulting in pitting;
[0046] Figure 8 The microscopic morphology of the pitting severity comparison example 2;
[0047] Fig. 9 The pit severity of comparative example 2 is a local enlargement of the pits in the comparative example to test the surface morphology of the pits;
[0048] Fig.10 This is the elemental analysis of the pitting of Comparative Example 3, which is a pitting severity comparison example. There are a large number of O, Mn, Si, and P precipitates at the pitting. DETAILED DESCRIPTION
[0049] Example 1-Example 6
[0050] A method for manufacturing a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with reduced edge pitting includes the following process steps: molten iron pretreatment → converter smelting → alloy fine-tuning station → RH → continuous casting → hot rolling → pickling and cold rolling → continuous annealing → hot-dip galvanizing.
[0051] Comparative Example 1-Comparative Example 3
[0052] A method for manufacturing a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with reduced edge pitting, the same as in the embodiment. Specific parameters are shown in Tables 1 to 4.
[0053] The composition of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel described in each embodiment and comparative example is shown in Table 1, and the remainder not shown in Table 1 is Fe and unavoidable impurities.
[0054] Table 1 Chemical composition of each example (wt%)
[0055] Example C Si Mn P Al Nb Ti B S N P / B Example 1 0.0012 0.035 0.30 0.043 0.031 0.011 0.022 0.0002 0.004 0.0020 215 Example 2 0.0026 0.060 0.40 0.042 0.058 0.019 0.030 0.0004 0.005 0.0010 105 Example 3 0.0011 0.030 0.32 0.044 0.033 0.017 0.021 0.0003 0.002 0.0025 147 Example 4 0.0028 0.065 0.39 0.039 0.052 0.012 0.029 0.0006 0.001 0.0022 65 Example 5 0.0012 0.040 0.31 0.035 0.032 0.015 0.025 0.0003 0.004 0.0017 117 Example 6 0.0027 0.070 0.38 0.045 0.055 0.018 0.022 0.0005 0.003 0.0028 90 Comparative Example 1 0.0014 0.060 0.32 0.044 0.033 0.017 0.027 0.0005 0.002 0.0025 88 Comparative Example 2 0.0019 0.050 0.36 0.041 0.033 0.017 0.022 0.0006 0.004 0.0025 68 Comparative Example 3 0.0020 0.090 0.45 0.040 0.037 0.019 0.023 0.0010 0.005 0.0017 40
[0056] The main steps of the production process of each embodiment and comparative example are:
[0057] The continuous casting produces a rectangular ingot with a thickness of 230 mm ± 5 mm, a length of 20 ± 2 m, and a width of 1500-1900 mm, and uses an oxygen-acetylene flame to clean the surface iron oxide scale of the six faces of the rectangular ingot, with a cleaning thickness of 2-3 mm, so as to prevent the surface iron oxide scale and inclusions from being pressed into the steel matrix during the subsequent rolling process;
[0058] For the hot rolling, the flame-cleaned slab is placed in a heating furnace for heating, and the furnace temperature is 1180-1210°C. Then, a rolling system of 6 rough rolling passes + 7 finishing rolling passes is adopted, and the finishing rolling temperature is controlled at 1050-1080°C, and the finishing rolling temperature within the range of 0-15cm of the edge is controlled at 1070-1100°C. After finishing rolling, the temperature within the range of 0-15cm of the edge is controlled at 920-935°C, and the temperature of the remaining parts is controlled at 910-925°C. The coiling adopts a laminar intensive cooling method, and the coiling temperature is controlled at 620-650°C; the Fe 2 O 3 Thickness ≤ 5μm, the entire iron oxide scale, including FeO+Fe 3 O 4 +Fe 2 O 3 Total thickness ≤10μm;
[0059] The pickling cold rolling, the straightening elongation is controlled at 1.5-2.5%, the hot coil is rolled into a thickness of 0.6-0.8mm by a five-stand rolling mill, the total reduction rate of the five stands is not less than 75% but not more than 82%, the roughness Ra of the steel plate after pickling is 0.4-0.8μm, the residual oil content at any position on the upper and lower surfaces is less than 100mg / L, the residual iron content is less than 50mg / L, and the pickling reflectivity at any position meets ≥75%;
[0060] The continuous annealing is that the above-mentioned acid-rolled coil is welded → edge digging → alkali solution brushing → electrolytic cleaning → hot water rinsing → drying and then enters the vertical full-radiant tube annealing furnace for annealing, the uniform heating time is 55-60s, the uniform heating temperature is controlled at 780-800°C, and the slow cooling rate is 5.95°C / s-6.7°C / s, slowly cooled to 600-660°C; then cooled to 470-490°C at a rapid cooling rate of 11.9°C / s-14.6°C / s; the dew point of the uniform heating section is -30--20°C, and the component of the protective atmosphere in the furnace during the entire annealing process is H 2 Volume content 5%, N 2 The volume content is 95%, the volume content of oxygen is guaranteed to be ≤10ppm, and the roughness Ra of the surface of the refractory bricks on the inner wall of the annealing furnace is controlled to be ≤0.3μm.
[0061] The temperature of the zinc pot is between 465 and 475℃, the dew point of the furnace nose is -6 to -3℃, and the temperature of the zinc pot is 453±2℃. The production method is 4 target rolls + 1 IF steel transition roll, using DC53D+Z, DC54D+Z, DC56D+Z or DC57D+Z IF steel transition rolls. After the steel coil production is completed, the surface is oiled, bundled and packaged.
[0062] The production process parameters of each embodiment are shown in Table 2-Table 4.
[0063] Table 2 Hot rolling process parameters of each embodiment
[0064]
[0065] Table 3 Pickling process parameters of each embodiment
[0066]
[0067]
[0068] Table 4 Annealing and galvanizing process of each embodiment
[0069]
[0070] The distribution of pitting on the edge of the surface and the structural properties of the products produced in each embodiment are shown in Table 5.
[0071] Table 5: Distribution of pitting spots on the edge of the product surface and structural properties produced in each embodiment
[0072]
[0073]
[0074] The data with horizontal lines in the above table are data that do not meet the requirements of the present invention.
[0075] According to the embodiment of the present invention, the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with a yield strength of 190 MPa produced by the present invention can meet the metallographic structure of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with a yield strength of 190 MPa for a thickness of 0.6 to 0.8 mm, which is ferrite, with an average grain size of 8.5 to 9.5, a grain size of 15 to 25 μm, and an "oxide film island" formed near the ferrite grain boundary with a diameter of ≤10 μm; the elongation after fracture is 38 to 45%, the work hardening rate n value is not less than 0.21, and the strain hardening exponent r 90 Not less than 2.0. There are no more than 2 pits with a diameter of ≤0.4mm in every 3 meters of strip steel within a width of 15cm on both sides of the steel plate. The surface quality meets the extremely stringent requirements of automotive panels, and has the advantages of simple production process operation, stable and reliable product quality, energy saving and emission reduction, and can be widely promoted and applied in galvanizing production lines.
[0076] The above description only provides a specific exemplary description of the present invention. It should be noted that the specific implementation of the present invention is not limited to the above method. As long as various non-substantial improvements are made using the technical concept and technical solution of the present invention, or the technical concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for manufacturing a thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel with reduced edge pitting, characterized in that: The manufacturing method comprises the following process flow: molten iron pretreatment → converter smelting → alloy fine-tuning station → RH → continuous casting → hot rolling → pickling and cold rolling → continuous annealing → hot-dip galvanizing; The hot rolling is heated to 1180-1210°C, the finishing rolling temperature is controlled at 1050-1080°C, the finishing rolling temperature within the range of 0-15cm of the edge is controlled at 1070-1100°C, the temperature within the range of 0-15cm of the edge after finishing rolling is controlled at 920-935°C, and the temperature of the remaining parts is controlled at 910-925°C; the coiling temperature is controlled at 620-650°C; The pickling cold rolling, the straightening elongation is controlled at 1.5-2.5%, the hot coil is rolled into a thickness of 0.6-0.8mm by a five-stand rolling mill, and the total reduction rate of the five stands is not less than 75% but not more than 82%; The continuous annealing has a uniform heating time of 55 to 60 seconds, a uniform heating temperature of 780 to 800°C, firstly slowly cooled to 600 to 660°C at a slow cooling rate of 5.95°C / s to 6.7°C / s, and then cooled to 470 to 490°C at a fast cooling rate of 11.9°C / s to 14.6°C / s, the dew point of the uniform heating section is -30 to -20°C, and the roughness Ra of the refractory brick surface of the inner wall of the annealing furnace is controlled to be ≤0.3μm; The thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel comprises the following components in mass percentage: C 0.001~0.003wt%, Si 0.03~0.07wt%, Mn 0.3~0.4wt%, Al 0.03~0.06wt%, P0.032~0.055wt%, B 0.0002~0.0006wt%, Nb 0.01-0.02wt%, Ti 0.02-0.03wt%, S≤0.006wt%, N≤0.003wt%, the balance is Fe and unavoidable impurities; The composition of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel satisfies: P / B=53~275.
2. The manufacturing method according to claim 1, characterized in that: The metallographic structure of the thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel is ferrite, the average grain size is 8.5-9.5, the grain size is 15-25 μm, and the "oxide film island" formed near the ferrite grain boundary has a diameter of ≤10 μm.
3. The manufacturing method according to claim 1 or 2, characterized in that: The thin-gauge hot-dip pure zinc-coated phosphorus-containing high-strength IF steel has a yield strength of ≥190 MPa, a tensile strength of ≥350 MPa, an elongation after fracture of 38-45%, a work hardening rate n value of not less than 0.21, and a strain hardening index r 90 Not less than 2.0; within the 15cm width range on both sides of the steel plate, there are no more than 2 pits with a diameter of ≤0.4mm in every 3 meters of strip steel.
4. The manufacturing method according to claim 1, characterized in that: The thickness of Fe2O3 on the outermost layer of the hot-rolled plate after coiling is ≤5μm, and the total thickness of the entire oxide scale, including FeO+Fe3O4+Fe2O3, is ≤10μm.
5. The manufacturing method according to claim 1, characterized in that: The roughness Ra of the steel plate after acid rolling is 0.4~0.8μm, the residual oil content at any position on the upper and lower surfaces is less than 100mg / L, the residual iron content is less than 50 mg / L, and the acid rolling reflectivity at any position meets ≥75%.
6. The manufacturing method according to claim 1, characterized in that: For the hot-dip galvanizing, the temperature of the zinc pot is between 465 and 475°C, the dew point of the furnace nose is -6 to -3°C, and the temperature of the zinc pot is 453±2°C.
7. The manufacturing method according to claim 1, characterized in that: The production method is 4 target rolls + 1 IF steel transition roll.
Citation Information
Patent Citations
Phosphorus-containing interstitial-free cold-rolled galvanized steel sheet, and manufacturing method thereof
CN106854729A
Structure-level color-coated base material hot-dip galvanized steel plate for thin-gauge steel product and manufacturing method thereof
CN111961789A